The contribution of veterinarians to the implementation of legislation on the protection of animals used for scientific purposes in Greece. - Zacharioudaki, Argyro; Kostomitsopoulos, Nikolaos (Journal of the Hellenic Veterinary Medical Society, 2022)
This article reviews the role of veterinarians in the implementation of Presidential Decree 56/2013, in harmonization to the European Directive 2010/63/EU, on the protection of animals used for scientific purposes in Greece. Veterinarians contribute to the implementation of the legislation as civil servants of the competent central and regional Veterinary Authorities, Designated Veterinarians of the breeder, supplier and user establishments, members of the Animal Welfare Bodies and Project Evaluation Committees, facility managers, researchers, teachers and trainers in laboratory animal science courses, and supervisors of competence of the personnel performing animal care and use procedures. Equally important is the participation of veterinarians as members of the National Committee for the Welfare of Animals Used for Scientific Purposes.